Differential regulation of glutamate transporter subtypes by pro-inflammatory cytokine TNF-α in cortical astrocytes from a rat model of amyotrophic lateral sclerosis. - Amélie O Dumont; Stéphanie Goursaud; Nathalie Desmet; Emmanuel Hermans (PLoS ONE, 2014)
Dysregulation of the astroglial glutamate transporters GLAST and GLT-1 has been implicated in several neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) where a loss of GLT-1 protein expression and activity is reported. Furthermore, the two principal C-terminal splice variants of GLT-1 (namely GLT-1a and GLT-1b) show altered expression ratio in animal models of this disease. Considering the putative link between inflammation and excitotoxicity, we have here characterized the influence of TNF-α on glutamate transporters in cerebral cortical astrocyte cultures from wild-type rats and from a rat model of ALS (hSOD1G93A). Contrasting with the down-regulation of GLAST, a 72 h treatment with TNF-α substantially increased the expression of GLT-1a and GLT-1b in both astrocyte cultures. However, as the basal level of GLT-1a appeared considerably lower in hSOD1G93A astrocytes, its up-regulation by TNF-α was insufficient to recapitulate the expression observed in wild-type astrocytes. Also the glutamate uptake activity after TNF-α treatment was lower for hSOD1G93A astrocytes as compared to wild-type astrocytes. In the presence of the protein synthesis inhibitor cycloheximide, TNF-α did not influence GLT-1 isoform expression, suggesting an active role of dynamically regulated protein partners in the adaptation of astrocytes to the inflammatory environment. Confirming the influence of inflammation on the control of glutamate transmission by astrocytes, these results shed light on the regulation of glutamate transporter isoforms in neurodegenerative disorders.